ANTAGONISTIC ACTIVITY OF PLANT GROWTH-PROMOTING RHIZOBACTERIA TO CONTROL RHIZOCTONIA SOLANI FUNGUS THAT CAUSES BLACK SCURF DISEASE IN POTATO - E. K. Abdul-Karim; S. N. Hawar; H. Z. Hussein (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The experiment was carried out in the season 2021-2022 at College of Agricultural Engineering Sciences / University of Baghdad, For testing the potential for the plant growth-promoting Rhizobacteria (PGPR) in controlling the Rhizoctonia solani fungus that causes black scurf disease in potatoes. All fungal isolates obtained a very good efficacy in the reduction seed germination percentage (0, 6.7, 15.6 and 17.7%, respectively) in comparison with control (97.7%). The results showed that the Rs1 and Rs4 fungi isolates are the most pathogenic as it recorded 5 and 4.2 respectively. Bl.4 bacterial isolate recorded the highest inhibitory ability of fungus growth (47.6%) with significant differences compared with Bl.5 and Bl.3, while Bl.2 achieved 5.53%. Based on the isolation and nucleotide sequencing, the highest inhibitory ability by bacteria isolated from soil (Bl.4) was achieved by Bacillus licheniformis. The results also showed the effectiveness of the immersion method with bacteria in reducing the severity of infection of the vegetative and root systems with R. solani, with reduction values of 26.67 and 30.00%, respectively, and significant differences compared with the control treatment (83.33, 88.33% respectively).